DOI: 10.1007/1-4020-4018-0_20
|View full text |Cite
|
Sign up to set email alerts
|

Utilization Of Salt-Affected Soils By Growing Some Acacia Species

Abstract: In Pakistan most of the salt affected areas are located in the heart of its agriculturally important tract of the Indus plain. Growing conventional crops in these problem lands is not economical but these could be utilized gainfully by growing salt tolerant trees or shrubs. However, there is a need to identify suitable species for such conditions. The present study was, therefore, undertaken to evaluate the performance of some local and exotic trees, belonging to Acacia species, in salt affected soils of Pakis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
12
0

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 11 publications
2
12
0
Order By: Relevance
“…In contrast to these findings, Shekhawat et al (2006) did not find any appreciable change in SAR with the cultivation of Salsola baryosma, Haloxylon recurvum and Suaeda nudiflora. However, studies with different species of Acacia and Atriplex also indicated that soil SAR decreased with cultivation of these species and effect of Acacia nilotica was more pronounced than others (Ashraf et al 2006a). Similarly, results of the experiments conducted with Sporobolus arabicus, Leptochloa fusca, Suaeda fruticosa, Atriplex lentiformis and Kochia indica also confirmed that cultivation of salt tolerant plants is effective in reducing the soil SAR (Ashraf 2007).…”
Section: Changes In Soil Chemical Characteristicssupporting
confidence: 58%
See 4 more Smart Citations
“…In contrast to these findings, Shekhawat et al (2006) did not find any appreciable change in SAR with the cultivation of Salsola baryosma, Haloxylon recurvum and Suaeda nudiflora. However, studies with different species of Acacia and Atriplex also indicated that soil SAR decreased with cultivation of these species and effect of Acacia nilotica was more pronounced than others (Ashraf et al 2006a). Similarly, results of the experiments conducted with Sporobolus arabicus, Leptochloa fusca, Suaeda fruticosa, Atriplex lentiformis and Kochia indica also confirmed that cultivation of salt tolerant plants is effective in reducing the soil SAR (Ashraf 2007).…”
Section: Changes In Soil Chemical Characteristicssupporting
confidence: 58%
“…According to Akhter et al (2004) addition of OM (8.2 g kg −1 of soil) after the cultivation of Kallar grass for 5 years, it reduced with the soil depth. Another study with Acacia species indicated that their cultivation on salt-affected soils increased the soil OM (Ashraf et al 2006a). Similarly, Aganga et al (2003) found an increase in soil OM with cultivation of Atriplex on salt-affected soils.…”
Section: Changes In Soil Chemical Characteristicsmentioning
confidence: 93%
See 3 more Smart Citations